Case report: A case of mycobacterium bovis, in a previously healthy 10-year-old girl in Lebanon - Amal Naous, MD; Zeina Naja, MD; Aref Ramadan, MD; Batoul Ahmad-Kassem, MD; Walaa Saba Tayon, MD; Mahmoud Abdelnabi, MD; Lynn Mansour; Zenah Delbani; Elissa El-judri; Ali Zeidan; Mariam Rajab, MD (Radiology Case Reports)
Mycobacterium Tuberculosis (M. TB) and Mycobacterium Bovis (M. Bovis), constituents of the Mycobacterium Tuberculosis complex (MTBC), pose diagnostic challenges due to shared extrapulmonary manifestations. This case portrays a patient initially treated for a fungal infection after presenting with weight loss, anorexia, and positive fecal occult blood. Subsequent hospitalization for continuous fever, limb edema, and strawberry tongue led to a diagnosis of Kawasaki disease. Despite treatment, symptoms persisted, prompting further investigation culminating in a Crohn's disease diagnosis and subsequent treatment initiation. However, symptom resolution remained elusive, prompting an urgent laparotomy where TB was confirmed via biopsies, despite earlier negative TB tests. This case underscores the diagnostic intricacies between Intestinal TB and Crohn's disease, emphasizing the necessity for heightened TB suspicion despite initial negative tests. The clinical overlap mandates meticulous diagnostic evaluations to avoid delayed or missed diagnoses.